2019
DOI: 10.2106/jbjs.cc.18.00091
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Hip Instability After Hip Arthroscopy: Is There a Role for Open Capsular Reconstruction?

Abstract: Case: A 23-year-old female athlete presented with postoperative hip pain and laxity following 3 arthroscopic hip procedures. Conclusions: Open reconstruction of the anterior hip capsule with Achilles allograft can correct arthroscopy-induced hip laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In previous reports, hip dislocation, after a low-energy trauma, occurred between 0 and 4 months postoperatively. These authors described both patient and surgical factors related to instability: female gender (77.8 %), acetabular dysplasia (22.2 %), and generalized ligamentous laxity (11.1 %), unrepaired capsulotomy (77.8 %), iliopsoas release (33.3 %), labrum repair or debridement, and acetabular and femoral remodeling [ 1 , 5 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, hip dislocation, after a low-energy trauma, occurred between 0 and 4 months postoperatively. These authors described both patient and surgical factors related to instability: female gender (77.8 %), acetabular dysplasia (22.2 %), and generalized ligamentous laxity (11.1 %), unrepaired capsulotomy (77.8 %), iliopsoas release (33.3 %), labrum repair or debridement, and acetabular and femoral remodeling [ 1 , 5 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost 3 % of patients require additional interventions for its treatment [ 4 ]. Female sex increased femoral anteversion, hip dysplasia, hyperlaxity, and traumatic injuries have been described as predisposing factors for iatrogenic hip instability [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic hip micro‐instability may be caused by capsular insufficiency secondary to capsular over‐resection, lack of capsular closure or cam over‐resection [1, 5, 8, 27, 43]. Two studies demonstrated significantly improved patient‐reported outcomes with capsular repair or plication for hip micro‐instability at a minimum of two‐year follow‐up [27, 43].…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent instability in all cases was resolved by the repair of the anterior capsule, suggesting an important stabilizing function of this ligament. 28 , 32 Another important feature of the ILFL is its microscopic composition, as when compared to the distinct characteristics of the LT and the ACL, the IL is a less specialized ligament, showing a lower level of collagen types I, III and IV, confirming its main role as a static stabilizer. 12 Similar results were confirmed by Sato et al, highlighting that the contents of elastic fibres are very rare in the ILFL, suggesting that the elastic fibre content does not relate to the functional significance of the ligament in the hip joint.…”
Section: Discussionmentioning
confidence: 99%